HUBUNGAN KARAKTERISTIK PEMULUNG DAN PENGGUNAAN ALAT PELINDUNG PERNAPASAN DENGAN KELUHAN GANGGUAN PERNAPASAN PADA PEMULUNG DI TPA JATIBARANG, SEMARANG - Riska Triafryani Putri; Tri Joko; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2017)
Solid waste is a curious problem because of every person produce waste from daily activities. Jatibarang landfill beside as place to collect solid waste, it also become source of livelihood’s scavengers. Everyday scavengers’ job directly related with waste, bad smell spread in landfill, air contaminats gas, and vector which bring diseases. The purpose of this study is to analyze relationship between scavengers characteristic and use of respiratory protective equipment with disorders on scavengers at Jatibarang landfill. The type of this study is analytic descriptive using cross sectional approach. The data collection technique of this study is accidental sampling technique. The samples are 75 scavengers and microbial air count with the type of microbial. The research was conducted by and laboratory examination, and interviewing using questionaire then analyzing with univariate and bivariate using chi-square. The result of this study showed that 80% scavengers suffered complaints of respiratory disorder. Chi-square analyze showed that there are not correlation between age (p value=0,058), gender (p value= 0,163), duration of work (p value= 0,460) with complaints of respiratory disorder. While, there are correlation between the length of work (p value= 0,039), smoking habit (p value=0,006), and use of respiratory protective equipment (p value= 0,001) with scavengers complaints of respiratory disorder. Air microbial amount in active zone is 1480 CFU/m3, waste collected place is 1600 CFU/m3, and scavengers house is 2520 CFU/m3. Identified microbes are fungi as Aspergillus sp, Mucor sp, Manillia sp, Bacillus sp, Staphylococcus epidermidis, Klebsiella oxytoca, Enterobacter aglomerans, Klebsiella ozaenae, Klebsiella pneumoniae. The conclusion is characteristic between scavengers related with respiratory disorder are the length of work, smoking habit, and complaint of respiratory disorder.